ANAEMIA: THE NEGLECTED FEMALE HEALTH PROBLEM IN DEVELOPING COUNTRIES - Nazir, Ghazala saimasaad2010@yahoo.com; Naz, Saima; Ali, Shafqut; Aziz, Shaheen; Malik, Shakeel Ahmad; Qari, Iftikhar Hossain; Irum, Samia (Journal of Ayub Medical College Abbottabad, 2011)
Background: Anaemia is arguably the biggest female health problems in developing countries. The world is still to fully fathom the extent and gravity of the problem. This problem aggravates particularly during and after pregnancies due to increased nutritional demands and inadequate iron supply and is therefore more widespread in parous segments of female population. Objective of this study was to determine prevalence of anaemia in apparently healthy parous female population of Abbottabad and investigate underlying causes. Methods: This descriptive, cross-sectional study was conducted from October 2001 to March 2011 in Abbottabad. Women reporting for various surgical procedures were investigated for anaemia by obtaining history through a structured performa, specifically designed to identify the underlying causes. Sixteen thousand women of child bearing age (20-40 years) were included in the study; 14,800 with history of at least one pregnancy and remaining with no previous pregnancy. Haemoglobin (Hb) was measured using haematology analyser Sysmex (KX21). Results: Of the screened women, 60% were found anaemic (Hb <12 g/dl) 10% of which were severely anaemic (Hb <6 g/dl). Anaemia was related to socio-demographic and obstetric history characteristics. The prevalence of anaemia was significantly lower in women who used iron supplements during their pregnancies. Lactating mothers not making up for the iron deficiencies during pregnancies usually carried their anaemia postpartum and beyond. Lower gaps between pregnancies also contributed significantly to the problem. Conclusion: Prevalence and severity of anaemia in reproductive age females reporting to surgical units were found to be exceptionally high. Frequency of anaemia in the parous females of relatively affluent city of Abbotabad indicates that anaemia may be on the rise in developing countries. Addressing pregnancy related anaemia and nutritional deficiencies through intake of supplements on regular basis in women before and between pregnancies is essential. Keywords: Anaemia, Reproductive age, nutritional deficiency, parous, Lactation